Interview: Björn Jakobsen - Björn M. Buttler Jakobsen (EXARC Journal, 2019)
Björn M Buttler Jakobsen has recently turned 70. He has worked presenting history and archaeology since the 1970s. His background is as an engineer, film maker, entrepreneur and he can also call himself marine archaeologist.